Mosquito larvicidal activities of Solanum villosum berry extract against the dengue vector Stegomyia aegypti - Chandra Goutam; Ghosh Anupam; Chowdhury Nandita (BMC, 2008)
Abstract Background Vector control is facing a threat due to the emergence of resistance to synthetic insecticides. Insecticides of botanical origin may serve as suitable alternative biocontrol techniques in the future. Although several plants have been reported for mosquitocidal activity, only a few botanicals have moved from the laboratory to field use, because they are poorly characterized, in most cases active principals are not determined and most of the works are restricted to preliminary screening. Solanum villosum is a common weed distributed in many parts of India with medicinal properties, but the larvicidal activity of this plant has not been reported so far. Methods Aqueous and polar/non-polar solvent extract of fresh, mature, green berries of S. villosum was tested against Stegomyia aegypti, a common vector of dengue fever. A phytochemical analysis of chloroform:methanol extract was performed to search for the active toxic ingredient. The lethal concentration was determined (log probit analysis) and compared with Malathion. The chemical nature of the active substance was also evaluated following ultraviolet-visual (UV-Vis) and infrared (IR) analysis. Results In a 72 hour bioassay experiment with the aqueous extract, the highest mortality was recorded in 0.5% extract. When the mortality of different solvent extracts was compared, the maximum (p < 0.05) mortality was recorded at a concentration of 50 ppm of chloroform:methanol extract (1:1, v/v). The larvicidal activity was lower when compared with the chemical insecticide, Malathion (p < 0.05). Results of regression analysis revealed that the mortality rate (Y) was positively correlated with the period of exposure (X) and the log probit analysis (95% confidence level) recorded lowest value (5.97 ppm) at 72 hours of exposure. Phytochemical analysis of the chlororm:methanol extract reported the presence of many bioactive phytochemicals. Two toxic compounds were detected having Rf = 0.82 (70% and 73.33% mortality in 24 and 48 hours, respectively) and Rf = 0.95 (40% and 50% mortality in 24 and 48 hours, respectively). IR analysis provided preliminary information about the steroidal nature of the active ingredient. Conclusion S. villosum offers promise as potential bio control agent against S. aegypti particularly in its markedly larvicidal effect. The extract or isolated bioactive phytochemical could be used in stagnant water bodies for the control of mosquitoes acting as vector for many communicable diseases.